Awareness of safe transfers in ambulance drivers after road traffic accidents - Mehta, Mitali S.; Ekbote, Amruta G. (International Journal Of Community Medicine And Public Health, 2023)
Background: Today accidents are among the leading causes of death. Deaths due to road traffic accidents are increasing at an alarming rate throughout the world. Hence, safe transfers become an important aspect to deal with. Ambulance drivers being the providers for this transfer should know about safe transfers and how is it performed. Methods: A validated self-structured questionnaire consisting of 14 questions related to knowledge about safe transfers was prepared and circulated to ambulance drivers via Google forms. Ethical approval and informed consent were taken. A total of 102 participants were included in the study and descriptive data analysis was done. Results: Out of 102 participants, 10.8% of drivers had attended a road trauma first aid course, 41.2% of participants had heard about safe transfers, 98% had transferred an RTA victim, 3.9% of participants knew the right way to transfer a patient with spinal injury, 37.3% of subjects knew how to transfer fracture cases, 96% of the participants knew safest way used for transferring a patient, 47.1% drivers knew about “golden hour”, 80.3% participants knew the correct way to transfer a traumatic patient, 22.5% of subjects knew the importance of safe transfers and 99% of drivers felt the need to learn about safe transfers. Conclusions: The study concludes that there is overall less awareness about safe transfers among ambulance workers. Although the willingness to learn about safe transfers is comparatively high. There is a need to increase awareness about safe transfers in ambulance drivers